2020
DOI: 10.1016/j.jor.2019.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local zoledronic acid administration in a rat model of posterolateral spinal fusion

Abstract: Study design: Randomized animal model study. Purpose: Posterolateral spinal fusion represents a common surgical procedure in the United States. The effect of bisphosphonate administration in these patients is poorly understood. The purpose of this study is to determine whether local administration of bisphosphonate by soaking bone autograft would affect the apparent bone density or structural properties of the fusion mass in a rat model of posterolateral spinal fusion. Methods: 36 Spring Dawley rats underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As seen in systemic ZOL treatment, the topical treatment of ZOL co-administration with rh-BMP-2 also promoted and maintained new bone formation in the bone marrow environment. Topical administration of ZOL has been considered to reduce the associated side effects and limit the effect to a target site [ 22 ]. ZOL is known to cause side effects such as hypocalcemia, renal failure, or osteonecrosis of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in systemic ZOL treatment, the topical treatment of ZOL co-administration with rh-BMP-2 also promoted and maintained new bone formation in the bone marrow environment. Topical administration of ZOL has been considered to reduce the associated side effects and limit the effect to a target site [ 22 ]. ZOL is known to cause side effects such as hypocalcemia, renal failure, or osteonecrosis of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…These doses fall within a range where previous studies have demonstrated a clinically significant treatment effect through local administration. 35 , 36 …”
Section: Methodsmentioning
confidence: 99%